Analisis Kesediaan Membayar (Willingness to Pay) Jasa Lingkungan pada Destinasi Ekowisata Umbul Manten di Kabupaten Klaten – Jawa Tengah - Deristani, Anggun; Hidayat, Agung (Center for Environmental Research, LPPM, Universitas Sebelas Maret, 2022)
Klaten Regency has natural and artificial tourism with the number of visitors reaching 1,399,167 people. One of the natural attractions, Umbul Manten, presents natural water baths that come out of the aquifer to the ground surface. Sustainable ecotourism development so that tourism management does not only prioritize temporary satisfaction or benefits for certain parties, but prioritizes environmental conservation and education. The purpose of this study is to calculate the value of willingness to pay (WTP) to support ecotourism and determine the factors that influence the value of WTP. Data processing using the Contingent Valuation Method (CVM) method, one of the methods for assessing the value of environmental services to determine WTP. The WTP value to support Umbul Manten ecotourism is IDR 2,600 (person/visit) and the total value of WTP (TWTP) to support Umbul Manten ecotourism is IDR 156,000. The WTP value of Umbul Manten tourism is influenced by age and income factors.